The factors affecting the performance of activated carbon prepared from oil palm empty fruit bunches for adsorption of phenol - Alam, Md. Zahangir (Elsevier, 2009)
Powdered activated carbons (PACs)were produced fromoil palmempty fruit bunches (EFB) by varying the operating parameters of temperatures, CO2 gas flow rates and activation times using 2-level full factorial experimental design. The EFB samples were first carbonized for 30 min using nitrogen gas followed by physical activation using CO2 to optimize best production conditions. The optimum conditions for PACs produced were investigated through adsorption tests on aqueous solution of phenol. The results of this studydemonstrated that the activation temperature with the range of 800–900 ◦C had themost significant effect on the adsorption characteristics aswell as the yield of the activated carbon produced. Based on the analysis of variance (ANOVA) and model equation developed, the optimum production conditions for the EFB PAC were found to be at the activation temperature of 900 ◦C with CO2 gas flow rate of 0.1 L/min and activation time of 15 min. Characterization of PAC produced showed that the activation conditions would find good-quality adsorbent with the BTE surface area of 345.1m2/g and well forming pores distribution